2022
DOI: 10.1097/md.0000000000029216
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between metabolic syndrome and follicle-stimulating hormone in postmenopausal women

Abstract: Depletion of ovarian reserve during menopausal transition raises follicle-stimulating hormone (FSH) markedly and menopause is related to an increased risk for metabolic syndrome (MetS). This study examined the relationship between FSH and MetS in postmenopausal women.We evaluated the anthropometric values, lipid profiles, high-sensitivity C-reactive protein (hs-CRP) level, Homeostasis model assessment for insulin resistance (HOMA-IR), and serum adipokines levels in 219 postmenopausal women. Serum FSH and estra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Besides these reproductive roles, FSH may also affect glucose metabolism. A recent systematic review suggests an inverse relationship between FSH levels and insulin resistance and a beneficial effect of FSH on glucose metabolism in postmenopausal women [31]. One of the studies discussed by this systematic review examined the relationship between FSH level, type 2 diabetes, and insulin resistance in postmenopausal women and found that higher FSH levels were associated with lower prevalence and incidence of type 2 diabetes and lower fasting insulin levels in this population [32].…”
Section: Follicle Stimulating Hormonementioning
confidence: 89%
“…Besides these reproductive roles, FSH may also affect glucose metabolism. A recent systematic review suggests an inverse relationship between FSH levels and insulin resistance and a beneficial effect of FSH on glucose metabolism in postmenopausal women [31]. One of the studies discussed by this systematic review examined the relationship between FSH level, type 2 diabetes, and insulin resistance in postmenopausal women and found that higher FSH levels were associated with lower prevalence and incidence of type 2 diabetes and lower fasting insulin levels in this population [32].…”
Section: Follicle Stimulating Hormonementioning
confidence: 89%
“…Chabrolle et al have demonstrated that ovarian adiponectin, adipoR1, and adipoR2 mRNA levels can be regulated by human chorionic gonadotropin (37). Additionally, a correlation between elevated FSH levels and improved insulin sensitivity has been reported, characterized by elevated adiponectin levels in the bloodstream (38). FSH has also been shown to promote ovulation by increasing the production of adiponectin in ovarian follicular fluid (39).…”
Section: Discussionmentioning
confidence: 99%
“…This is caused by a change in hormonal secretion due to a decrease in ovarian function. From the menopausal transition to menopause, diminished ovarian function leads to hormonal changes characterized by decreases in reproductive hormones, including estrogen, progesterone, testosterone, and inhibin B ( 47 ). Depletion of ovarian reserve during the menopausal transition raises follicle-stimulating hormone (FSH) markedly.…”
Section: Discussionmentioning
confidence: 99%